Testowanie koncepcji nowych produktów w niemieckich przedsiębiorstwach sprzętu gospodarstwa domowego - Dąbrowski, Dariusz (New Products Concept Testing in German Enterprises of Household Appliances, 2006)
This article presents concept testing - one of important marketing research techniques undertaken within new product development - on a basis of mail survey carried out among 56 German producers of household appliances. The study results indicate that a majority of firms survey plied concept testing to a large extent. Moreover, with respect to firms surveyed, it appeared that applying concept testing is positively related to new product outcomes as well as to company's size.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 431-438